2020
DOI: 10.3389/fpsyg.2020.01714
|View full text |Cite
|
Sign up to set email alerts
|

Growth Modeling in a Diagnostic Classification Model (DCM) Framework–A Multivariate Longitudinal Diagnostic Classification Model

Abstract: A multivariate longitudinal DCM is developed that is the composite of two components, the log-linear cognitive diagnostic model (LCDM) as the measurement model component that evaluates the mastery status of attributes at each measurement occasion, and a generalized multivariate growth curve model that describes the growth of each attribute over time. The proposed model represents an improvement in the current longitudinal DCMs given its ability to incorporate both balanced and unbalanced data and to measure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The relationship between DCMs and L-DCMs is similar to the relationship between LCA and LTA and between BN and DBN. L-DCMs represent a relatively new area of research but several recent examples exist in the literature (Kaya & Leite, 2017; Li et al, 2016; Madison & Bradshaw, 2018; Pan et al, 2020; Wang et al, 2018; Zhan et al, 2019). Several of these studies have included sample size as a manipulated factor.…”
Section: Overview Of Dynamic Bayesian Networkmentioning
confidence: 99%
“…The relationship between DCMs and L-DCMs is similar to the relationship between LCA and LTA and between BN and DBN. L-DCMs represent a relatively new area of research but several recent examples exist in the literature (Kaya & Leite, 2017; Li et al, 2016; Madison & Bradshaw, 2018; Pan et al, 2020; Wang et al, 2018; Zhan et al, 2019). Several of these studies have included sample size as a manipulated factor.…”
Section: Overview Of Dynamic Bayesian Networkmentioning
confidence: 99%
“…To provide theoretical support for the concept of a longitudinal learning diagnosis, several longitudinal learning diagnosis models (LDMs) have been proposed in recent years (for a review, see Pan, Qin, & Kingston, 2020; Zhan, 2020b). Existing longitudinal LDMs can be divided into two main types: latent transition analysis‐based models (e.g., Kaya & Leite, 2017; Li, Cohen, Bottge, & Templin, 2016; Madison & Bradshaw, 2018; Wang, Yang, Culpepper, & Douglas, 2018; Wen, Liu, & Zhao, 2020; Zhang & Wang, 2019) and higher‐order latent structure‐based models (e.g., Lee, 2017; Lin, Xing, & Park, 2020; Huang, 2017; Pan et al., 2020; Zhan, 2020c; Zhan, Jiao, Liao et al., 2019). The former estimates the transition probabilities from one latent attribute (profile) to another or the same latent attribute (profile).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Huang (2017) proposed a multilevel generalized deterministic input noisy and-gate model (G-DINA; de la Torre, 2011) that captures changes in discrete latent attributes via a multilevel structure where the discrete attributes are assumed to come from a common continuous latent trait. Pan et al (2020) extended Huang (2017) and employed a multivariate normal distribution for the higher order traits and assessed proficiency changes under the log-linear cognitive diagnostic model (LCDM; Henson et al, 2009). Zhan, Jiao, Liao, et al (2019) employed a similar strategy in the development of a higher-order longitudinal variant of the DINA model (Junker & Sijtsma, 2001;Macready & Dayton, 1977;Maris, 1999), and Zhan, Jiao, Man, et al (2019) demonstrated how to estimate the longitudinal DINA model under a Bayesian setting.…”
Section: Introductionmentioning
confidence: 99%